Implementasi Sistem Inventaris Berbasis Web dalam Optimalisasi Manajemen Barang - Ditasari, Widda Aulia; Nugraha, Gavin Azarya (JATISI, 2025)
The development of modern business requires efficient and accurate inventory management to support operational activities. Many stores still face difficulties in recording stock manually, which can lead to recording errors and delays in ordering. This study aims to design and develop a Web-Based Inventory Information System for Tokodigitalan to make data management processes more efficient and accurate. The system was developed using the Prototyping method, which allows users to be directly involved in the development process through iterative evaluation of the prototype. The system design employs the Unified Modeling Language (UML) to illustrate the structure and workflow of the system. Implementation was carried out using PHP (Laravel) and MySQL as the database, with a responsive web-based interface. Testing was conducted using the Black Box Testing method to ensure that the system functions properly according to user requirements. The test results show that the system can record transactions accurately and accelerate the recording process compared to manual methods. The implementation of this web-based inventory system makes inventory management more efficient, administration more organized, and supports the smooth operation of the store. This study emphasizes the importance of applying information technology in inventory management to improve the effectiveness of retail businesses.